Hubungan Antara Stres Dengan Kualitas Tidur Pada Mahasiswa Yang Sedang Menyusun Skripsi Di Universitas “X” - Gina, Fathana; Putra, Alvin Rahma; Fahrudin, Adi (Peneliti.net, 2023)
This research is motivated by various sleep problems experienced by each individual, in this case, final year students who are preparing their thesis. Students are required to complete their thesis in order to obtain a bachelor's degree, but during the drafting process there are many obstacles which in the end make students difficult in the drafting process, so that it can have an impact on individual cognition which in this case is stress on students so that it affects sleep activities at night . The purpose of this study was to find out whether there is a relationship between stress and sleep quality in students who are preparing their thesis at “X” University. The method used is correlational quantitative. The subjects in this study were students who were compiling their thesis at